Numerical study on behavior of bolted shear connector used in composite cold-formed steel beams. (August 2022) - Hosseinpour, Mahmoud; Zeynalian, Mehran; Daei, Maryam; Ataei, Abdoreza
Abstract: The use of concrete slab in cold-formed steel (CFS) beams can not only increase the ultimate resistance, but also can prevent their lateral buckling. Since the formation of composite action in this type of beams requires the use of appropriate shear connectors, in this paper, an extensive numerical study was conducted to investigate the behavior of 8.8 grade bolted connectors in CFS composite beams. For this purpose, at the first, advanced numerical models of concrete-CFS section connections were developed. Geometric details, material nonlinearities, material damage models and loading protocols were carefully simulated. Next, the results obtained from the numerical models were validated in detail against the experimental results. It was proved that the developed models have the ability to simulate the behavior of the 8.8 grade bolted connectors in these connections. At the end, an extensive parametric numerical study consisting of 216 connections was conducted. The examined parameters included CFS thickness, CFS ultimate strength, concrete compressive strength, embedded bolt's height and bolt diameter. Consequently, the effect of each of these parameters on the ultimate strength, ductility as well as the failure modes of the bolted shear connectors was carefully investigated. Highlights: Structural performance of CFS-concrete composite beams is investigated. Numerical study was conducted to study the CFS composite beams. 216 connections were studied. Geometric details, material nonlinearities, and loading protocols were simulated.